Hyper IgM syndrome presenting as chronic suppurative lung disease - Montella Silvia; Maglione Marco; Giardino Giuliana; Di Giorgio Angela; Palamaro Loredana; Mirra Virginia; Ursini Matilde; Salerno Mariacarolina; Pignata Claudio; Caffarelli Carlo; Santamaria Francesca (BMC, 2012)
Abstract The Hyper-immunoglobulin M syndromes (HIGM) are a heterogeneous group of genetic disorders resulting in defects of immunoglobulin class switch recombination. Affected patients show humoral immunodeficiency and high susceptibility to opportunistic infections. Elevated serum IgM levels are the hallmark of the disease, even though in few rare cases they may be in the normal range. Hyper IgM is associated with low to undetectable levels of serum IgG, IgA, and IgE. In some cases, alterations in different genes may be identified. Mutations in five genes have so far been associated to the disease, which can be inherited with an X-linked (CD40 ligand, and nuclear factor-kB essential modulator defects) or an autosomal recessive (CD40, activation-induced cytidine deaminase, and uracil-DNA glycosylase mutation) pattern. The patient herein described presented with recurrent upper and lower respiratory infections and evidence of suppurative lung disease at the conventional chest imaging. The presence of low serum IgG and IgA levels, elevated IgM levels, and a marked reduction of in vivo switched memory B cells led to a clinical and functional diagnosis of HIGM although the genetic cause was not identified.